2019
DOI: 10.1021/acs.inorgchem.8b02898
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of Hg(II) Ions in Aqueous Medium Using Zinc-Based Metal–Organic Framework

Abstract: Here we describe, a simple solution and solid-state sensor for the ultrasensitive detection of Hg­(II) ions in both standardized and environmental samples through changes of fluorescence intensity of a zinc-based metal–organic framework (MOF). The MOF is highly water stable in a wide pH range from 4 to 11. The lower detection limit of Hg2+ is 10–11 M with a very high binding constant of 1.011 × 109 M–1 s–1. It also exhibits a high selectivity toward mercury ion in the presence of other interfering metal ions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…Metal ion sensors NH 2 -MIL-125(Ti) Pb 2+ 0.70 × 10 −2 nM 5 [405] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Fe 3+ 3.24 µM 5 [406] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Al 3+ 1.31 µM 5 [406] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Cr 3+ 1.84 µM 5 [406] MOF NU-902 Cd 2+ 0.3 ppb [407] MOF NU-902 PVC membrane Cd 2+ [407] CAU-10-V-H Pd 2+ 110 nM 5 [408] MIL-53(Al)–NH2-MPA Fe 3+ 0.36 µM [416] [[Zn(4,4′-AP)(5-AIA)]. (DMF)0.5] n Hg 2+ 0.01 nM [409] b. Anion sensors TMU-41 Cr 2 O 7 2− 0.02 µM 4 [410] TMU-41 CrO 4 2− 0.03 µM 4 [410] TMU-41 MnO 4 − 0.03 µM 4 [410] ...…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal ion sensors NH 2 -MIL-125(Ti) Pb 2+ 0.70 × 10 −2 nM 5 [405] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Fe 3+ 3.24 µM 5 [406] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Al 3+ 1.31 µM 5 [406] [Cd(Hcip)(bpea) 0.5 (H 2 O)] n (Cd-CP) Cr 3+ 1.84 µM 5 [406] MOF NU-902 Cd 2+ 0.3 ppb [407] MOF NU-902 PVC membrane Cd 2+ [407] CAU-10-V-H Pd 2+ 110 nM 5 [408] MIL-53(Al)–NH2-MPA Fe 3+ 0.36 µM [416] [[Zn(4,4′-AP)(5-AIA)]. (DMF)0.5] n Hg 2+ 0.01 nM [409] b. Anion sensors TMU-41 Cr 2 O 7 2− 0.02 µM 4 [410] TMU-41 CrO 4 2− 0.03 µM 4 [410] TMU-41 MnO 4 − 0.03 µM 4 [410] ...…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
“…Mercury ions can cause fatal poisoning. For their detection, Mandal’s group developed a new Zn-based MOF, [Zn(4,4′-AP)(5-AIA)]·(DMF) 0.5 , that shows selective and sensitive detection of Hg 2+ in aqueous media [409] . The authors reported that the MOF could detect picomolar concentrations of Hg 2+ ions, with a LOD of 9.9 × 10 −12 M. This is one of the lowest values ever reported.…”
Section: Upcoming Mofs Applications For Future Commercializationmentioning
confidence: 99%
“…(DMF) 0.5 ] n is highly water stable, which provides very low detection limit of Hg 2+ as low as 10 −11 M with a very high binding constant of 1.011 × 10 9 M −1 s −1. [103] Interestingly, the boric acid (BA)-functionalized lanthanide MOF, BA-Eu-MOF, provides an efficient sensor for detection of Hg 2+ and CH 3 Hg + ions Reprinted with permission from ref. [ 268 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The soft acid Hg 2+ ion has a higher affinity toward a soft base like N. The above MOF is highly water stable, providing a lower detection limit of Hg 2+ as low as 10 −11 M with a very high binding constant of 1.011 × 10 9 M −1. [103] It also exhibits a high selectivity toward mercury ion in the presence of other interfering metal ions. [103] Furthermore, Zn-based MOF, Zn-APA (APA is 5-aminoisophthalic acid), features a 3-D supramolecular network with uncoordinated carboxylic oxygen atoms, exhibiting a fast fluorescence response to Hg 2+ ion over other metal ions in aqueous solutions.…”
Section: Mercury Detectionmentioning
confidence: 99%
See 1 more Smart Citation